The limited rationality of technology - Agassi, Joseph (2019)
Ingemar Nordin$1 (Bs Using Knowledge: On the Rationality of Science, Technology, and Medicine is a critical rationalist examination of medicine as a social system, largely science-based, but including quackery. Thus rationality is limited, as befits the author$1 (Bs fallibilism. - Reproduced.s